Foundations of Analytical Chemistry A Teaching-Learning Approach - Valcárcel Cases, Miguel (Springer International Publishing, 2018)
This book offers a completely new approach to learning and teaching the fundamentals of analytical chemistry. It summarizes 250 basic concepts of the field on the basis of slides. Each of the nine chapters offers the following features: • Introduction: Summary. General scheme. Teaching objectives. • Text containing the explanation of each slide. • Recommended and commented bibliography. • Questions to be answered. • Slides. A distinct feature of this novel book is its focus on the fundamental concepts and essential principles of analytical chemistry, which sets it apart from other books presenting descriptive overviews of methods and techniques.